Implementasi Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf Di Kecamatan Pringsurat - Kurniandini, Sholeh; Adi Widodo Putro, Danang; Sariyekti , Eko (El-Qenon: Journal of Islamic Law, 2024)
From this fundamental issue, some of the purposes of this research were found, among them to evaluate the implementation of the Law 41 of 2004 on Wakaf in Pringsurat district. The research uses qualitative descriptive research methods, i.e., a strategy for collecting information from the source field which is subsequently presented in the form of a detailed and original story from the interview that is obtained and then performed interpretation of the data, as well as using other documents as a supplement. The sources used in this research are primary and secondary. The results of this study indicate that the implementation of Law No. 41 of 2004 on Wakaf in Pringsurat district was hampered by a lack of understanding of the law and its functions. Many societies are unaware of the law and its implications so vulnerable to conflict between heirs and society. Pringsurat has proposed a number of measures to improve the implementation of the law and its functions, among others, the appointment of KUA officers, socialization of the basic duties and functions of the Nazhir, assistance of the service on the setting up and administration of the Wakaf